The Implications of Instagram Platform for Arabic Vocabulary Acquisition - Agustina, Rahmah Fadhilah; Harsita, Destia; Chairani, Ully Shifa (UIN Syekh Wasil Kediri, Indonesia, 2023)
Social media is a digital platform connected to the internet network. Social media also plays an important role in facilitating community communication and access to information. Of the various social media that are popular among millennials now, Instagram is an application that can increase Arabic vocabulary. The purpose of this study is to analyze and describe the implications of the Instagram platform for acquiring Arabic vocabulary. This research uses qualitative research, and the type is descriptive-qualitative. The data collection techniques used are documentation and interviews. Based on the results of the research analysis, it can be concluded that Instagram is the most popular account for acquiring Arabic vocabulary, supported by three features: feeds, Instagram stories, and reels, which can have significant implications because Instagram has provided a lot of Arabic content that can be used as material for learning Arabic, especially vocabulary. The availability of Arabic content can make it easier for Arabic learners to add relatively new vocabulary, and it can be accessed anytime and anywhere. This research implies that it can provide information to the public, especially educational practitioners. This research can provide information that, in the activity of obtaining vocabulary, can be easily found anywhere and anytime, especially through Instagram social media. Instagram can provide benefits by providing information in the form of vocabulary, which can make it easier for Arabic language learners to acquire new vocabulary